Antiprotozoal activity of medicinal plants used by Iquitos-Nauta road communities in Loreto (Peru) - Vásquez-Ocmín P. (2018)
The authors thank the Consejo de Ciencia y Tecnología del Perú (CONCYTEC) (Council for science and technology of Peru) (299 - 2014 - FONDECYT) for the Ph.D. scholarship (PGVO). Authors are indebted to the communities cited in this work for their essential contribution in order to spread their ancestral knowledge in favor of science. We also appreciate the important collaboration of Lizardo Fachin Malaverri, Stéphanie Denis, Dennis del Castillo Torres and Juan Vásquez Briones